2021
DOI: 10.1042/bcj20210376
|View full text |Cite
|
Sign up to set email alerts
|

C-type cytochrome-initiated reduction of bacterial lytic polysaccharide monooxygenases

Abstract: The release of glucose from lignocellulosic waste for subsequent fermentation into biofuels holds promise for securing humankind's future energy needs. The discovery of a set of copper dependent enzymes known as lytic polysaccharide monooxygenases (LPMOs) has galvanized new research in this area. LPMOs act by oxidatively introducing chain breaks into cellulose and other polysaccharides, boosting the ability of cellulases to act on the substrate. Although several proteins have been implicated as electron source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 82 publications
2
11
0
1
Order By: Relevance
“…What remains unclear, however, is whether LPMOs may have reducing-agent specificity in addition to substrate specificity (Frommhagen et al, 2016;Meier et al, 2018). Askarian and coworkers demonstrated that CbpD chitinolytic activity was enhanced by ascorbate and the redox-active compound pyocyanin, which is secreted by P. aeruginosa (Askarian et al, 2021), and Branch and coworkers demonstrated that a c-type cytochrome can activate the celluloseactive CjAA10B in Cellvibrio japonicus (Branch et al, 2021). CbpD and other LPMOs may favor reductants that are secreted by their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…What remains unclear, however, is whether LPMOs may have reducing-agent specificity in addition to substrate specificity (Frommhagen et al, 2016;Meier et al, 2018). Askarian and coworkers demonstrated that CbpD chitinolytic activity was enhanced by ascorbate and the redox-active compound pyocyanin, which is secreted by P. aeruginosa (Askarian et al, 2021), and Branch and coworkers demonstrated that a c-type cytochrome can activate the celluloseactive CjAA10B in Cellvibrio japonicus (Branch et al, 2021). CbpD and other LPMOs may favor reductants that are secreted by their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…To probe this hypothesis, we studied the modification of CjX183-D, a naturally occurring cytochrome from Cellvibrio japonicus which does not contain any lysine residues. 22 N-terminal selectivity was compared to the mutant CjX183-D R51K, in which a single lysine had been installed (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…A single X158 has been characterised to date but it, as well as many other distantly-related domains, have been purified with the well-known redox molecule ubiquinone-8 bound, as revealed by their crystal structures [ 80 ]. In addition, Cbp2D is also predicted to contain cytochrome-like domains at the C-terminus of the protein, which would suggest a likely electron-transfer function, hence, an interest in them as potential LPMO electron donors [ 78 , 81 ]. In our own recent work, we were able to isolate one of the cytochrome-like domains ( Cj X183D) from Cbp2D and showed that it was likely an electron transferring, as opposed to catalytic, c -type cytochrome [ 81 ].…”
Section: Protein-based Electron Donors From Bacteriamentioning
confidence: 99%
“…In addition, Cbp2D is also predicted to contain cytochrome-like domains at the C-terminus of the protein, which would suggest a likely electron-transfer function, hence, an interest in them as potential LPMO electron donors [ 78 , 81 ]. In our own recent work, we were able to isolate one of the cytochrome-like domains ( Cj X183D) from Cbp2D and showed that it was likely an electron transferring, as opposed to catalytic, c -type cytochrome [ 81 ]. Its reduced state was able to drive LPMO catalysis in the presence of O 2 but activity in the presence of H 2 O 2 was not considered at the time.…”
Section: Protein-based Electron Donors From Bacteriamentioning
confidence: 99%